2021
DOI: 10.1128/msphere.00875-21
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding Lactobacillus paracasei and Streptococcus oralis Biofilm Interactions through Agent-Based Modeling

Abstract: We previously discovered a role of the oral commensal Streptococcus oralis as an accessory pathogen. S. oralis increases the virulence of Candida albicans infections in murine oral candidiasis and epithelial cell models through mechanisms which promote the formation of tissue-damaging biofilms. Lactobacillus species have known inhibitory effects on biofilm formation of many microbes, including Streptococ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The detection rates of Lactobacillus and Streptococcus were significantly higher in the 8020N group than in the 8020Y group. Lactobacillus may act with Streptococcus, becoming highly pathogenic and causing tissue injury [32]. A previous study indicated that an increase in the salivary Lactobacillus count was associated with more tooth defects [33], and this was considered to be a contributing factor to the decrease in the number of teeth in this study.…”
Section: Discussionmentioning
confidence: 55%
“…The detection rates of Lactobacillus and Streptococcus were significantly higher in the 8020N group than in the 8020Y group. Lactobacillus may act with Streptococcus, becoming highly pathogenic and causing tissue injury [32]. A previous study indicated that an increase in the salivary Lactobacillus count was associated with more tooth defects [33], and this was considered to be a contributing factor to the decrease in the number of teeth in this study.…”
Section: Discussionmentioning
confidence: 55%
“…This species has been associated with several potential beneficial effects on human health. Some of the notable beneficial effects attributed to L. paracasei include promoting digestive health, supporting the immune system, balancing gut microbiota, managing allergies, maintaining skin health, alleviating gastrointestinal disorders, promoting oral health, reducing oxidative stress, and improving bone health [ 36 , 37 , 38 , 39 , 40 ]. L. paracasei ET-66 was a strain currently isolated from human breast milk in 2016 and exhibited a beneficial effect on oral health [ 23 , 24 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1963, the literature documented the isolation of B. longum from human feces [4]. In 2002, Sakata et al, based on gastrointestinal disorders, promoting oral health, reducing oxidative stress, and improving bone health [36][37][38][39][40]. L. paracasei ET-66 was a strain currently isolated from human breast milk in 2016 and exhibited a beneficial effect on oral health [23,24,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Given the difficulties associated with representing these intricacies using equation-based approaches, alternative model types, such as agent-based models (ABMs), frequently serve as the foundation for medical digital twins [3][4][5][6][7][8][9][10][11]. In biomedical applications, agents in an ABM represent biological entities such as cells in a tissue or microbes in a biofilm [12][13][14][15]. The behavior of agents is usually described by stochastic rules, which allow them to navigate heterogeneous spatial environments and interact with each other.…”
mentioning
confidence: 99%